Evaluation of Bone Marrow- and Brain-Derived Neural Stem Cells in Therapy of Central Nervous System Autoimmunity - Yang, Jingxian (American Society for Investigative Pathology, 2010)
Adult subventricular zone (SVZ)-derived neural stem cells (NSCs) have therapeutic effects in experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis. However, SVZ precursor cells as a source of NSCs are not readily accessible for clinical application. In the present study, we demonstrate that NSCs derived from bone marrow (BM) cells exhibit comparable morphological properties as those derived from SVZ cells and possess a similar ability to differentiate into neurons, astrocytes, and oligodendrocytes both in vitro and in vivo. Importantly, both types of NSCs suppressed chronic experimental autoimmune encephalomyelitis to a comparable extent on transplantation. Mechanisms underlying the therapeutic effects of NSCs include immunomodulation in the periphery and the central nervous system (CNS), neuron/oligodendrocyte repopulation by transplanted cells, and enhanced endogenous remyelination and axonal recovery. Furthermore, we provide evidence for the trans-differentiation of transplanted BM-NSCs into neural cells in the CNS, while no fusion of these cells with host neural cells was detected. This is the first study that directly compares SVZ- versus BM-NSCs with regard to in vivo neural differentiation and anti-inflammatory and therapeutic effects on CNS inflammatory demyelination. Their virtually identical therapeutic potential, greater accessibility, and autologous properties make BM-NSCs a novel and highly applicable substitute for SVZ-NSCs in cell-based multiple sclerosis therapies.